2010
DOI: 10.1086/656367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunological Cross‐Reactivity between Clade A9 High‐Risk Human Papillomavirus Types on the Basis of E6‐Specific CD4+Memory T Cell Responses

Abstract: CD4(+) T cell responses against the E6 oncoprotein of human papillomavirus (HPV) type 16 and 5 closely related members of clade A9 (HPV31, 33, 35, 52, and 58) were charted in peripheral blood mononuclear cell cultures from healthy subjects and patients who underwent HPV16 E6/E7-specific vaccination. Initial analyses with overlapping peptide arrays showed that approximately one-half of the responding subjects displayed reactivity against corresponding E6 peptides from >or=2 HPV types. This suggested immunologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Previously we reported that there are highly conserved domains in HPV E2 protein sequence among different HPV genotypes, which could lead to cross-reactivity between the E2 peptides of different types of HPV [13,14]. However, cross-reactive T cells to HPV16 E6 are rare [40] suggesting that the responses observed in these children most likely reflect true circulating HPV16-specific memory T-cells during their early childhood. The authors consider that rather perplexing, because all these children were sexually inexperienced.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we reported that there are highly conserved domains in HPV E2 protein sequence among different HPV genotypes, which could lead to cross-reactivity between the E2 peptides of different types of HPV [13,14]. However, cross-reactive T cells to HPV16 E6 are rare [40] suggesting that the responses observed in these children most likely reflect true circulating HPV16-specific memory T-cells during their early childhood. The authors consider that rather perplexing, because all these children were sexually inexperienced.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a cross-reactivity of HPV16 E2, E6, and E7 peptides with T-cells specific to other closely related HPV types is conceivable, albeit a rarely observed event [3, 4, 33, 40]. …”
Section: Discussionmentioning
confidence: 99%
“…Invasive cervical cancer (ICC) provides an ideal system to investigate the relation of immunological mechanisms to tumor etiology and progression. The etiological agent, high risk human papillomavirus (hr-HPV), is known [7], its E6 and E7 genes encode tumor specific epitopes that can be recognized by immune T lymphocytes to cause cell destruction [8-11], and expression of these epitopes is intimately associated with the neoplastic transformation [12], a situation similar to that in rodent tumors caused by the polyoma virus, where neoplastic variants lacking the virus encoded cellular antigen could not be isolated by immunoselection [13]. Furthermore, the lesions preceding ICC are well defined, including cervical intraepithelial neoplasia (CIN) grades 1, 2, and CIN3/carcinoma in situ (CIS) [14-18], and archived cervical samples are available from women at different stages of the disease.…”
Section: Introductionmentioning
confidence: 99%